Provenance experiment with spruce (Picea abies (L.) Karst. and Picea obovata (Ledeb.)) in the North of Russia (Arkhangelsk region) - Elena N. Nakvasina; Alexey G. Volkov; Nadezhda A. Prozherina (Folia Forestalia Polonica, 2017)
This research presents the variability in the survival and growth for 27 provenances of spruce ( Picea abies (L.) Karst. and Picea obovata (Ledeb.)). All the tests were carried out in Russia, Arkhangelsk region, 62º 54’ N, 40º 24’ E, in the northernmost site of the State Geographic Network, established in 1977. For the research on the spruce provenances, standard methods for studying the geographic variation of the main forest-forming species were used. Growth rates of provenances were correlated with their geographical coordinates and climatic characteristics. Data was expressed in standard deviation units to select the best in growth provenances. Despite the significant differences in the location of the original stands (up to 12º N and 37º E), variability in survival, height and diameter is low (coefficient of variation is 12.2–19.0%). Obtained data indicated that provenances’ growth is correlated on longitude of the location rather than on the latitude. Diameter and average height of provenances significantly depend on annual rainfall. The height of provenance is mostly dependent on the location of the initial habitats and their climatic characteristics. It is also related to the length of the growing season and the air temperature (annual average and in January). Groups of the provenances of the best and the worst growth were distinguished. The group of the best ones on the integral indicator (volume stand) includes provenances of the western origin represented by P. abies and its immediate hybrids – Karelia (3), Vologda (24), Leningrad (5), Pskov (7) and Moscow (29) Regions – and provenances of the eastern one represented by P. obovata – Komi (26) and Perm (38) Region. High plasticity of spruce ( P. abies (L.) Karst. × P. obovata (Ledeb.)), growing within the Russian Plain, in sufficiently favourable conditions of middle taiga subzone (Arkhangelsk Region, Russia) was proved.